2023
DOI: 10.3389/fmed.2023.1156254
|View full text |Cite
|
Sign up to set email alerts
|

Genetically predicted green tea intake and the risk of arterial embolism and thrombosis

Abstract: BackgroundIn previous observational studies, green tea intake has been demonstrated to protect against arterial embolism and thrombosis. However, whether there is a causative connection between green tea intake and arterial embolism and thrombosis is currently unclear.MethodsA two-sample Mendelian randomization (MR) study has been designed to explore whether there is a causal association between green tea intake and arterial embolism and thrombosis by acquiring exposure and outcome data from previously publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…By contrast, no significant difference of D-dimer change was observed between the two groups. From the clinical perspective of the efficacy of green tea intake on thrombotic diseases, only a study provided causal evidence between genetically predicted green tea intake and the prophylaxis of arterial embolism and thrombosis ( 9 ). The present study is the first one that provides clinical evidence for the prophylactic efficacy of green tea intake in the development of VTE among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, no significant difference of D-dimer change was observed between the two groups. From the clinical perspective of the efficacy of green tea intake on thrombotic diseases, only a study provided causal evidence between genetically predicted green tea intake and the prophylaxis of arterial embolism and thrombosis ( 9 ). The present study is the first one that provides clinical evidence for the prophylactic efficacy of green tea intake in the development of VTE among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the green tea group, patients were subdivided into subgroups according to the average volume of green tea they drank per day. Based on the previous literature ( 9 ), all patients in the green tea group were classified into subgroup 1 (0–250 mL per day), subgroup 2 (250–500 mL per day), and subgroup 3 (500 mL or more per day) in the present study, according to the self-reported average volume of green tea that they drank per day. In China, tea brewing is typically conducted by infusing 2–3 grams of loose tea leaves in a cup containing 100–150 mL hot water with a temperature of 85–100°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Mendelian randomization study showed that tea consumption can reduce the risk of arterial thrombosis [ 36 ]. Besides, there seems to be a lack of sufficient research on the relationship between tea consumption and DVT.…”
Section: Discussionmentioning
confidence: 99%